2022
DOI: 10.3389/fimmu.2022.1013531
|View full text |Cite
|
Sign up to set email alerts
|

The commonness in immune infiltration of rheumatoid arthritis and atherosclerosis: Screening for central targets via microarray data analysis

Abstract: BackgroundAlthough increasing evidence has reported an increased risk of atherosclerosis (AS) in rheumatoid arthritis (RA), the communal molecular mechanism of this phenomenon is still far from being fully elucidated. Hence, this article aimed to explore the pathogenesis of RA complicated with AS.MethodsBased on the strict inclusion/exclusion criteria, four gene datasets were downloaded from the Gene Expression Omnibus (GEO) database. After identifying the communal differentially expressed genes (DEGs) and hub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 90 publications
1
5
0
Order By: Relevance
“…Monocytes as a type of circulation blood cells have been proven in many studies to relate to sarcopenia and osteoporosis ( Deng et al, 2021 ; Nie et al, 2022 ; Zeng et al, 2022 ). Consistent with previous studies used different kind of specimens ( Wang Z. et al, 2022 ; Liu J. et al, 2022 ; Mo et al, 2022 ), we have concluded that the intersection between gene expression maps of muscle tissues and monocytes may provide us much wider insights into the development of osteosarcopenia ( Liu et al, 2017 ). In our study, key crosstalk genes ( ARHGEF10 , PCDH7 , CST6 , and ROBO3 ) were identified by DEG analysis, WGCNA, and machine learning methods, and then validated by independent datasets and clinical samples.…”
Section: Discussionsupporting
confidence: 89%
“…Monocytes as a type of circulation blood cells have been proven in many studies to relate to sarcopenia and osteoporosis ( Deng et al, 2021 ; Nie et al, 2022 ; Zeng et al, 2022 ). Consistent with previous studies used different kind of specimens ( Wang Z. et al, 2022 ; Liu J. et al, 2022 ; Mo et al, 2022 ), we have concluded that the intersection between gene expression maps of muscle tissues and monocytes may provide us much wider insights into the development of osteosarcopenia ( Liu et al, 2017 ). In our study, key crosstalk genes ( ARHGEF10 , PCDH7 , CST6 , and ROBO3 ) were identified by DEG analysis, WGCNA, and machine learning methods, and then validated by independent datasets and clinical samples.…”
Section: Discussionsupporting
confidence: 89%
“…In the etiology of AS, the chemokine receptor CXCR4 is notably present across a diverse range of cellular entities implicated in CVD, encompassing ECs, Vascular Smooth Muscle Cells (VSMCs), T-cells, B-cells, neutrophils, monocytes, and macrophages. 71 Investigations spearheaded by Merckelbach et al 96 have illuminated a marked upsurge in the transcriptional and protein concentrations of CXCR4 and CXCL12 within carotid atherosclerotic plaques, as contrasted with normative vascular structures. 97,98 Further substantiation from zoological research delineates CXCR4's contributory role in AS, evidencing that its augmented expression within murine cardiac tissue amplifies infarct dimensions, diminishes myocardial efficiency, and catalyzes the influx of pro-inflammatory cellular units.…”
Section: Discussionmentioning
confidence: 99%
“…In the etiology of AS, the chemokine receptor CXCR4 is notably present across a diverse range of cellular entities implicated in CVD, encompassing ECs, Vascular Smooth Muscle Cells (VSMCs), T‐cells, B‐cells, neutrophils, monocytes, and macrophages 71 . Investigations spearheaded by Merckelbach et al 96 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T regs maintain immune homeostasis by releasing immunosuppressive cytokines, including IL-10 and TGF-b, or directly inhibiting proinflammatory cytokine production from monocytes and macrophages. Thus, T reg cells play a protective role in AS, and their deficiency is associated with a significant increase in atherosclerotic lesions ( 34 ). Consistent with the previous conclusion, the immune infiltration analysis revealed a significantly decreased proportion of T reg cells in AS patients.…”
Section: Discussionmentioning
confidence: 99%